The Institute of Acquisitive Prescription in Lithuania: Pathways ant Pitfalls - Darčkutė, Gabija; Fominova, Kamilia Edita (Vilnius University Open Series, 2024)
This article analyzes the concept of the institute of acquisitive prescription, its purpose, conditions of application and occurance in practice, the legal acts that were in force in Lithuania in the past, the sources of Roman era and the jurisprudence. The work points out that in the era of Roman private law domination, the understanding of the acquisitive prescription is distinctive from what we have today. Nevertheless, the institute of acquisitive prescription is interpreted through the prism of prescription as an actual state. The work also discusses the problematic aspects of the institute: the exclusive inviolability of state property is questioned, the controversial nature of the absence of registration as a condition of legality. Taking into account the stated drawbacks of the institute, its possible changes and the associated possible benefits for both the state and people are also foreseen.